Self administered cognitive screening test (TYM) for detection of Alzheimer's disease: cross sectional study. (4th June 2009) - Brown, Jeremy; Pengas, George; Dawson, Kate; Brown, Lucy A; Clatworthy, Philip
Abstract : Objective To evaluate a cognitive test, the TYM ("test your memory"), in the detection of Alzheimer's disease. Design Cross sectional study. Setting Outpatient departments in three hospitals, including a memory clinic. Participants 540 control participants aged 18-95 and 139 patients attending a memory clinic with dementia/amnestic mild cognitive impairment. Intervention Cognitive test designed to use minimal operator time and to be suitable for non-specialist use. Main outcome measures Performance of normal controls on the TYM. Performance of patients with Alzheimer's disease on the TYM compared with age matched controls. Validation of the TYM with two standard tests (the mini-mental state examination (MMSE) and the Addenbrooke's cognitive examination-revised (ACE-R)). Sensitivity and specificity of the TYM in the detection of Alzheimer's disease. Results Control participants completed the TYM with an average score of 47/50. Patients with Alzheimer's disease scored an average of 33/50. The TYM score shows excellent correlation with the two standard tests. A score of ≤42/50 had a sensitivity of 93% and specificity of 86% in the diagnosis of Alzheimer's disease. The TYM was more sensitive in detection of Alzheimer's disease than the mini-mental examination, detecting 93% of patients compared with 52% for the mini-mental state exxamination. The negative and positive predictive values of the TYM with the cut off of ≤42 were 99% and 42% with a prevalence of Alzheimer's disease of 10%. Thirty one patients with non-Alzheimer dementias scored an average of 39/50. Conclusions The TYM can be completed quickly and accurately by normal controls. It is a powerful and valid screening test for the detection of Alzheimer's disease.